CONCEPTUAL ASPECTS OF SOCIAL RESPONSIBILITY OF BUSINESS AND PROSPECTS OF ITS PRACTICAL IMPLEMENTATION IN UKRAINE - Vanina , Y. A; Kosenko , А. V (Theory and Practice of Public Administration, 2021)
The article presents the results of research and generalization of the theoretical foundations of social responsibility of business and substantiation of priorities for the development of the domestic CRB model. The definition of “social responsibility of business” is defined, which is defined as the responsible attitude of any company to its product or service, to consumers, employees, partners; active social position, which consists in harmonious coexistence, interaction and constant dialogue with society, participation in solving the most acute social problems. The differences between the terms “social responsibility of business” and “corporate social responsibility” are revealed. The main models of corporate social responsibility are highlighted. The main differences in the areas of manifestation, objects and measures of social responsibility of business of different countries have been identified.The high level of development of corporate social responsibility in the countries of the European Union, the USA and Japan has been proved, which is the result of a long purposeful state policy aimed at making entrepreneurs aware of their role in the socio-economic development of society.Publications of annual social reports on corporate social responsibility (CSR-reports) as a basic tool for informing consumers and society are described.The ratings of the best CSR programs implemented in the world and in Ukraine are researched and generalized.It is established that corporate social responsibility in Ukraine is in its infancy. The peculiarities of the Ukrainian model of corporate social responsibility include: lack of basic principles of responsible behavior of enterprises throughout the country, weak motivation for such practices, lack of state support for the formation of the institutional environment for socially responsible business.Factors influencing the formation and development of social responsibility of Ukrainian business are identified. These include: economic (unformed institutional environment of business, concentration of capital in government, inefficient implementation of economic policy, significant public debt, high inflation and inflation expectations, high interest rates) and non-economic (specific mentality of the population, declining normality), lack of censorship mechanisms in the media and Internet resources, a high level of criminalization of society).It is proved that in the process of formation and implementation of social responsibility of entrepreneurship the state should use the necessary levers to influence the formation of the institutional environment by stimulating initiatives to implement effective tools of international standardization, business social reporting, environmental and financial monitoring of companies.Among the basic incentives for the development of social responsibility of entrepreneurship in Ukraine are identified effective interaction between government and business, their bilateral productive dialogue and optimization of the process of fulfilling the social function of enterprises in society.